Fundamentals of Electrical Circuit Analysis - Salam, Md. Abdus (Springer Singapore, 2018)
This book is designed as an introductory course for undergraduate students, in Electrical and Electronic, Mechanical, Mechatronics, Chemical and Petroleum engineering, who need fundamental knowledge of electrical circuits. Worked out examples have been presented after discussing each theory. Practice problems have also been included to enrich the learning experience of the students and professionals. PSpice and Multisim software packages have been included for simulation of different electrical circuit parameters. A number of exercise problems have been included in the book to aid faculty members.